Ранняя группа личных украшений салтовского населения Подонцовья (по материалам погребений с фибулами Нетайловского могильника) - Аксёнов, В. С. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryV. Aksyonov. The early group of personal adornments of the Saltov Podontsovye population (accoding to burial with fibulas from the Netaylivha burial ground)During last years in the Netaylivka burials were discovered 8 fibulas belonging to the 2 types. Type 1 is a T-shaped hinged brooch with rectangular flap on the case, with an elongated plate-like stalk. Type 1 is a swivel T-shaped brooch with rectangular scutellum and an elongate plates pin. Type 2 formed by a swivel T-brooches with trapezoidal plates arched body and flat spatula-shaped pin. Type 1 fibulas are similar to excavated ones on the monuments of 8th — 9th centuries from Ossetia, Dagestan, Chechnya and Ingushetia. Type 2 fibulas probably they are a variant of swivel fibulae with a flat spatula-shaped pin represented on the monuments of North-Eastern Caucasus from 3–4 centuries AD and got here the development.Personal adornments discovered with the brooches suggest the existence of 2 sets of metal ornaments. The difference in the sets is chronological. Burial with the grave goods of the first set are dated from the middle VIII th century to the late of VIII th centuries AD. The second set dated from the late of VIII th — early of IX th centuries AD.Key words: the Saltova-Mayatshaya culture, the Netaylivha burial ground, fibula, personal adornments, the Stolbiche-Starohorsynshaya horizon.